Frontispiece: An Integrated Imaging Probe Design: The Synthesis of 99mTc/Re‐Containing Macrocyclic Peptide Scaffolds. Issue 2 (7th January 2015) - Hickey, Jennifer L.; Simpson, Emily J.; Hou, Jinqiang; Luyt, Leonard G.
<x xml:space="preserve">Abstract</x> Metal Scaffolding With the proper design, cyclic peptides may act as scaffolds emulating β‐sheet regions, enabling investigation into molecular recognition and protein aggregation. In their Full Paper on page 568 ff., L. G. Luyt et al. report on the synthesis of peptide macrocycles, which have been stitched together through a pyridyl tridentate chelation core, followed by metal coordination using 99mTc or Re tricarbonyl. Structural analysis revealed that the peptide backbone exists in a similar conformation both before and after metal incorporation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>